Conference European Investigation Order: Practical Dilemmas and Theoretical Considerations, Book of Extended Abstracts, 8. & 9. December 2020, online (University of Maribor Press, 2021)
This publication contains abstracts of contributions presented at the conference "European Investigation Order – Practical Dilemmas and Theoretical Considerations", which was held online on 8th and 9th of December 2020. Practitioners and academics from multiple EU Member States shared best practices and identified key shortcomings of the European Investigation Order. The event was executed as an integral part of the EU JUST project “European Investigation Order – Legal Analysis and Practical Dilemmas (EIP-LAPD)”, coordinated by the University of Maribor. The structure of the publication roughly follows the agenda of the conference. In the first part the future of mutual recognition and judicial cooperation in criminal matters in the EU is addressed. The second part is more closely focused at the European Investigation Order. Some theoretical dilemmas as well as practical considerations are presented. Lastly, some national reports which were drafted as a key deliverable of the EIO-LAPD project are also outlined.